A method for assessing resilience of high-speed EMUs considering a network-based system topology and performance data. (October 2021) - Lin, Shuai; Jia, Limin; Zhang, Hengrun; Wang, Yanhui
The high complexity of the system topology and the uncertainty of threats necessitate the consideration of the resilience of high-speed electric multiple units (EMUs). This paper first gives a definition of high-speed EMU resilience. Then, the structure of a high-speed EMU is described in the form of a network to enable the application of network science for resilience evaluation based on corresponding mathematical expressions. Afterward, a measure of system performance (MSP) is constructed that considers the influence of the high-speed EMU topology and performance data. According to the definition of resilience of a high-speed EMU, a system resilience measurement (SRM) is proposed that comprehensively considers the degree and time of the change in system performance. The validity of our method is then illustrated by applying it to the system topology and performance data associated with the Chinese standard electric multiple units (CEMUs) that serve on high-speed railways in China. Experiments are reported to illustrate the concept of resilience and the procedure for its measurement and to present comparisons with an existing resilience index. Our results indicate that the SRM proposed here can capture the sensitivity of the response of high-speed EMUs to the disturbances, thereby supporting the optimal design and risk management.